Prognostic factors for disability and sick leave in patients with subacute non-malignant pain: a systematic review of cohort studies. Issue 1 (6th January 2016) - Valentin, Gitte H; Pilegaard, Marc S; Vaegter, Henrik B; Rosendal, Marianne; Ørtenblad, Lisbeth; Væggemose, Ulla; Christensen, Robin
Abstract : Objective: This systematic review aims to identify generic prognostic factors for disability and sick leave in subacute pain patients. Setting: General practice and other primary care facilities. Participants: Adults (>18 years) with a subacute (≤3-month) non-malignant pain condition. Eligibility criteria were cohort studies investigating the prediction of disability or long-term sick leave in adults with a subacute pain condition in a primary care setting. 19 studies were included, referring to a total of 6266 patients suffering from pain in the head, neck, back and shoulders. Primary and secondary outcome measures: The primary outcome was long-term disability (>3 months) due to a pain condition. The secondary outcome was sick leave, defined as 'absence from work' or 'return-to-work'. Results: PubMed, EMBASE, CINAHL and PEDro databases were searched from 16 January 2003 to 16 January 2014. The quality of evidence was presented according to the GRADE WG recommendations. Several factors were found to be associated with disability at follow-up for at least two different pain symptoms. However, owing to insufficient studies, no generic risk factors for sick leave were identified. Conclusions: Multiple site pain, high pain severity, older age, baseline disability and longer pain duration were identified as potential prognostic factors for disability across pain sites. There was limited evidence that anxiety and depression were associated with disability in patients with subacute pain, indicating that these factors may not play as large a role as expected in developing disability due to a pain condition. Quality of evidence was moderate, low or very low, implying that confidence in the results is limited. Large prospective prognostic factor studies are needed with sufficient study populations and transparent reporting of all factors examined. Trial registration number: CRD42014008914.